PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS QUIZIZZ DAN GOOGLE SLIDES - Bahar , Afdi Fauzul; Dewi , Bella Tasya Kumala; Mansur, Ejah Said; Siregar, Maria Ulfah (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2024)
The COVID-19 pandemic has revolutionized the learning process, including online learning which requires educators to be more adaptive and innovative in teaching. Educators, especially teachers, must master the latest technology and learning methods, especially with the challenges in the post-pandemic era, where students tend to prefer the Learning by Doing approach. This community service activity is a Quizizz and Google Slides training for Teachers at SMA Abu Bakar IT Yogyakarta. The target of this activity is 22 educators who are community service partners. Activities are carried out offline or face-to-face consisting of presentation of materials and practices and evaluation of activities by providing training activity questionnaires. The research method used is Asset-Based Community Development (ABCD). This method can optimize organization, connect and utilize assistance from external institutions. The results of the questionnaire responses given to participants for this training activity showed positive results, this was felt because the teacher gained skills and knowledge in using the Quizizz and Google Slides platforms. ========================================== Pandemi Covid-19 telah membuat revolusi proses pembelajaran, diantaranya adalah proses pembelajaran daring yang mengharuskan para pendidik untuk lebih adaptif dan inovatif dalam pengajarannya. Tenaga pendidik khususnya guru perlu menguasai teknologi dan metode pembelajaran terkini, terutama dengan adanya tantangan di era pasca pandemi, siswa cenderung menyukai pendekatan Learning by Doing. Kegiatan pengabdian ini diwujudkan dalam bentuk pelatihan Quizizz dan Google Slides bagi para guru di SMA IT Abu Bakar Yogyakarta. Sasaran dari kegiatan ini adalah 22 Tenaga Pendidik yang merupakan mitra pengabdian. Kegiatan dilakukan secara luring yang terdiri dari pemaparan materi dan praktek serta evaluasi kegiatan dengan memberikan angket kegiatan pelatihan. Metode penelitian yang digunakan adalah Asset-Based Community Development (ABCD). Metode tersebut mampu untuk mengoptimalkan pengorganisasian, menghubungkan serta memanfaatkan bantuan dari lembaga eksternal. Hasil respon angket yang diberikan kepada peserta pelatihan ini menunjukan hasil yang positif, para guru mendapatkan keterampilan dan pengetahuan dalam penggunaan Platform Quizizz dan Google Slides.